Societal Collapse and Psychological Resilience: A Social Scientific Reading of Collective Trauma in Mary Shelley's The Last Man - Zela, Granit (European Journal of Social Science Education and Research, 2025)
Mary Shelley's dystopian novel The Last Man (1826), while a cornerstone of literary studies, offers a profound and underutilized historical imaginary for understanding contemporary societal crises. This article moves beyond traditional literary criticism to reframe Shelley's work as a sociological and educational case study, particularly relevant in the post-COVID-19 era. Using a theoretical framework grounded in the sociology of collective trauma and social cohesion, this analysis investigates the novel's depiction of a "narrative plague"—the collapse of shared meaning, social bonds, and institutional trust—that runs parallel to the medical pandemic it portrays. The study employs a qualitative textual analysis to examine the social-psychological dimensions of isolation, loss, and anomie as depicted in the novel. Findings reveal how the narrative simulates the disintegration of social capital and the failure of political and scientific institutions to manage catastrophe, offering critical insights into the foundations of community resilience and mental health. This 19th-century text is analyzed as a pre-sociological thought experiment, connecting historical representations of societal collapse with contemporary social science discourse on disaster response and recovery. The article argues that the novel's themes have direct implications for educational policy and pedagogy, highlighting the urgent need for trauma-informed approaches that can rebuild social inclusion, foster critical media literacy, and cultivate psychological resilience in an era of profound informational and social fragmentation.
Keywords: Mary Shelley, The Last Man, social cohesion, collective trauma, educational resilience, social capital, narrative plague, post-pandemic studies, social policy, mental health